Principal's Leadership Strategy in Strengthening Character Education - Badrun Badrun; Fitrah Sugiarto; Arnis Rachmadhani; Hendra SH (Sekolah Tinggi Agama Islam Al Hidayah, 2022)
This study aims to determine leadershipPrincipals in developing character education in Madrasah Ibtidaiyah Negeri 2 Mataram City and the factors that become obstacles for Principals in developing character education in Madrasah Ibtidaiyah Negeri 2 Mataram City. The research approach used in this research is a qualitative approach. The research subjects were the principal, teachers and students. Determination of research subjects is done by using a purpose sampling technique. Data collection techniques were carried out using interviews, observation, and documentation. This type of data analysis uses the Miles and Huberman model, namely data reduction, data display, and conclusion drawing/verification data. The principal's role as a leader in the school is in the form of conducting continuous guidance in the development of education, namely: first, character modeling, the madrasa principal encourages all teachers and administrative staff to be good character models for all students. second, teaching (teaching), regular and continuous communication with madrasa residents regarding the realization of character education in madrasas. third, good character strengthening (reinforcing) for all school members (teachers, students, and administrative staff). This caring attitude is implemented by involving teachers in making various democratic decisions. good character strengthening (reinforcing) for all school members (teachers, students, and administrative staff). This caring attitude is implemented by involving teachers in making various democratic decisions. good character strengthening (reinforcing) for all school members (teachers, students, and administrative staff). This caring attitude is implemented by involving teachers in making various democratic decisions.